2012
DOI: 10.1039/c2dt31526b
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrous acid: controversy and consensus surrounding an enigmatic oxidant

Abstract: The isomerisation of ONOOH to NO(3)(-) and H(+), some oxidations and all hydroxylations and nitrations of aromatic compounds are first-order in ONOOH and zero-order in the compounds that are modified. These reactions are widely believed to proceed via homolysis of ONOOH into HO˙ and NO(2)˙ to an extent of ca. 30%. We review the evidence pro and contra homolysis in studies that involve (1) thermochemical considerations, (2) isomerisation to NO(3)(-) and H(+), (3) decomposition to NO(2)(-) and O(2), (4) HO˙ scav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 117 publications
4
53
0
Order By: Relevance
“…This modification can be generated through several pathways that include the reaction with ROS and RNS like ONOO − and NO 2 • [225227] (Figure 2). NO • generated by NOS can react with O 2 •− to form ONOO − that, at acidic pH, is present as protonated form (ONOOH) which is believed to decompose into HO • and NO 2 • to an extent of ~30% [10]. Generally, tyrosine oxidation is a two-step process with the formation of a tyrosine radical, generated by different oxidative steps, followed by the reaction with NO 2 • .…”
Section: Markers Based On Ros-induced Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This modification can be generated through several pathways that include the reaction with ROS and RNS like ONOO − and NO 2 • [225227] (Figure 2). NO • generated by NOS can react with O 2 •− to form ONOO − that, at acidic pH, is present as protonated form (ONOOH) which is believed to decompose into HO • and NO 2 • to an extent of ~30% [10]. Generally, tyrosine oxidation is a two-step process with the formation of a tyrosine radical, generated by different oxidative steps, followed by the reaction with NO 2 • .…”
Section: Markers Based On Ros-induced Modificationsmentioning
confidence: 99%
“…Upon activation, neutrophils produce various ROS via myeloperoxidase (MPO) and RNS via inducible nitric oxide synthase (iNOS). MPO catalyzes the H 2 O 2 -dependent formation of hypochlorous acid (HClO) while iNOS produces nitric oxide (NO • ), which then reacts with O 2 •− to form peroxynitrite (ONOO − ) [10]. NOX associated with cell membrane catalyzes the generation of superoxide radicals that play a physiological role in cancer invasion, hypoxia, and integrin signaling [1113].…”
Section: Introductionmentioning
confidence: 99%
“…The exact pathway of ONOO − and ONOOH (peroxynitrous acid) decay to NO − 2 and NO − 3 at neutral pH is still debated (Table 3). It was suggested that ONOOH isomerises to NO − 3 and H + either directly or indirectly via the radical intermediates NO 2 and OH (Goldstein and Merenyi, 2008; Koppenol et al, 2012). The peroxynitrite anion on the other hand yields the RNS NO 2 , NO, and N 2 O 3 during its degradation to NO − 2 (Goldstein and Merenyi, 2008).…”
Section: Interactions Between No and Rosmentioning
confidence: 99%
“…OH) 24,26 with an efficiency of approximately 30%, though these values are controversial. 48,50,51 The hydroxyl radical is reactive enough to remove electrons from nearly any biological molecule, for instance the reaction with tyrosine creates a tyrosyl radical which can then react with nitrogen dioxide to form nitrotyrosine. In addition, peroxynitrite directly reacts with CO 2 yielding nitrosoperoxycarbonate (ONOOCO 2 À), which decomposes into nitrogen dioxide and the carbonate radical (…”
Section: Oxidative Modifications By Peroxynitritementioning
confidence: 99%